IDEOLOGY OF DISASTER EDUCATION TRAUMA HANDLING POST-EARTHQUAKE IN PICTURE STORIES BOOK: CRITICAL DISCOURSE ANALYSIS - Damayanti, Silvia; Suarka, I Nyoman; Banda, Maria Matildis; Purnawati, Ketut Widya (International Review of Humanities Studies, 2024)
This research analyzes the ideology that the author intends to instill in picture storybooks for children in Japan. The study aims to explore how the author conveys the ideology of handling trauma in children after earthquake disasters. The objects of the study are two picture storybooks titled "Yuzuchan" and "Yappari Ouchi Ga Ii Na." The research was conducted qualitatively using the documentary data search method. The analysis was carried out with van Dijk's CDA theory and Peirce's Semiotics Theory. The results of the analysis reveal that "Yuzuchan" and "Yappari Ouchi Ga Ii Na" are picture storybooks produced to help children cope with post-earthquake trauma. Disaster education handling the trauma is distributed in Macro Structure, Superstructure, and Microstructure. Although both of them deliver disaster education to overcome the same trauma, because the two authors have different backgrounds, the goals of the post-disaster ideology to be conveyed are different, the themes raised, and the topics raised are different. To convey the ideology of dealing with the trauma of death in Yuzuchan's story, the author raised the theme of loss due to catastrophic death. While at "Yappari Ouchi Ga Ii Na", from the ideology of disaster education facing trauma healing the ideology of earthquake trauma. The ideology of earthquake trauma handling is reflected in the macro and micro structures in both picture story discourses. The author uses diction and atmosphere to depict the post-earthquake trauma experienced by the characters. Meanwhile, disaster education in the form of trauma handling is conveyed through schematic elements, settings, presuppositions, diction, sentence patterns, and rhetoric in the stories. This research is not only beneficial for learners of the Japanese language and literature implementing CDA theory in discourse but also valuable for authors seeking to create stories about post-disaster trauma handling.